2021
DOI: 10.1186/s12935-021-02317-9
|View full text |Cite
|
Sign up to set email alerts
|

A paradoxical role for sestrin 2 protein in tumor suppression and tumorigenesis

Abstract: Sestrin 2, a highly conserved stress-induced protein, participates in the pathological processes of metabolic and age-related diseases. This p53-inducible protein also regulates cell growth and metabolism, which is closely related to malignant tumorigenesis. Sestrin 2 was reported to regulate various cellular processes, such as tumor cell proliferation, invasion and metastasis, apoptosis, anoikis resistance, and drug resistance. Although sestrin 2 is associated with colorectal, lung, liver, and other cancers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…In exercised mice, Crisol et al [24] have reported that sestrin-1 expression in muscle was increased when acute exercise was performed, whereas chronic exercise provoked its diminution. Likewise, contradictory results have been described for sestrin-2 and tumor pathology, since bidirectional functions (as tumor-suppressing and oncogene) have been found for this protein in various cancer types [46].…”
Section: Discussionmentioning
confidence: 99%
“…In exercised mice, Crisol et al [24] have reported that sestrin-1 expression in muscle was increased when acute exercise was performed, whereas chronic exercise provoked its diminution. Likewise, contradictory results have been described for sestrin-2 and tumor pathology, since bidirectional functions (as tumor-suppressing and oncogene) have been found for this protein in various cancer types [46].…”
Section: Discussionmentioning
confidence: 99%
“…2) Sestrin 2 is a probable biomarker and therapeutic target for tumor treatment that plays a vital role in the incidence and development of malignance. Some studies identified sestrin 2 as a tumor suppressor gene, while others described it as an oncogene ( Qu et al, 2021 ). A previous study found that the expression of SESN2 was positively associated with the IC50 of sorafenib in HCC cell lines and Sestrin 2 could induce sorafenib primary resistance by activation of the AKT and AMPK pathways ( Dai et al, 2018 ).…”
Section: Sorafenib Resistancementioning
confidence: 99%
“…Sestrin (SESN) is a highly conserved protein encoded by genes whose cell expression is up-regulated when exposed to DNA damage, oxidative stress and hypoxia (Qu et al, 2021). It includes three isoforms: SESN1, SESN2, and SESN3 (Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…; SESN2 activates the AMPK pathway and inhibits downstream mTORC1-P70S6K to promote autophagy (Peng et al, 2014;Wolfson et al, 2016). Similar to autophagy, the role of SESN2 in tumors is paradoxical (Qu et al, 2021). Some studies have found that SESN2 is a tumor suppressor gene, such as neuroblastoma (Ambrosio et al, 2017), bladder cancer (Liang et al, 2016), colorectal cancer (Wei et al, 2015), and endometrial cancer (Shin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%